Glass fiber and graphene reinforced polymer rod and production method thereof
By combining graphene nanosheets with polyester resin, it is used to manufacture glass fiber reinforced polymer rods with high tensile strength and elastic modulus, the problems of high material costs and insufficient stress in the prior art are solved, and low Cost, high-performance polymer rods, suitable for civil engineering fields.
Patent Information
- Application Number
- CN202280096190.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-20
- Publication Date
- 2025-01-07
AI Technical Summary
Existing glass fiber reinforced polymer rods are difficult to withstand greater stress in increasingly demanding reinforced structures and are costly to produce, requiring a new material with low cost and high mechanical properties.
The polyester resin reinforced by graphene nanosheets is combined with glass fibers to create polymer rods with higher tensile strength and elastic modulus through a pultrusion process, replacing high added value resins such as epoxy resins.
The same or higher mechanical properties as the prior art are achieved, the production costs are reduced, and more competitive products are provided, suitable for high-demand civil engineering applications, and can replace some steel bars to build a lighter structure.
Smart Images

Figure CN119278231A_ABST
Abstract
Description
Technical Field
[0001] The present invention generally relates to the field of manufacturing reinforced polymer rods for use in civil engineering. In an additional embodiment, the present invention relates to a method for producing a polymer rod comprising glass fibers and a resin reinforced with graphene nanoplatelets for use in the field of civil engineering. Background Art
[0002] Different types of polymer rods are known in the art for reinforcing structures, in particular for use in the field of civil engineering. In particular, long structures such as polymer support rods produced from fibers and coated with thermosetting resins such as polyester, vinyl ester and epoxy resins are well known and widely used by those skilled in the art.
[0003] In general, fiber reinforced polymers (FRPs) are produced from structural resins such as polyester, vinyl ester and epoxy resins, which cover flexible, continuous solid reinforcing fibers of small cross-section relative to their length. Glass fibers are obtained by melting inorganic glass; basalt fibers are obtained by melting basalt; carbon fibers are produced by pyrolysis of organic precursor fibers and contain at least 90% carbon by mass; and aramid fibers are produced from linear fiber-forming polyamides in which at least 85% of the amide groups are directly attached to two aromatic rings.
[0004] There are several standards governing the use of these products, the following are of particular relevance to this technology:
[0005] ISO 14406-1:2015;
[0006] ACI 440.1R-15 - European Union;
[0007] ASHTO LFRP2009-EU;
[0008] GOST 31938-2012 - Russia;
[0009] CAN / CSA -S806-02-Canada;
[0010] CNR-DT-Italy;
[0011] Technical Committee CT 303 - IBRACON-ABECE-GT 03 - Reinforced concrete structures made of unconventional materials - Brazil.
[0012] In the prior art there are found several polymeric rods produced from resins and glass fibres, to which reference will be made below to define the prior art.
[0013] Chinese patent application CN113969042, titled "Cerium oxide-graphene oxide modified GFRP (glass fiber reinforced polymer) tendons and preparation method thereof", filed on November 30, 2021, describes a glass fiber reinforced polymer comprising high silica glass fibers, wherein a plurality of glass fiber units are coated and impregnated with a vinyl resin containing cerium oxide and graphene oxide in its components.
[0014] Chinese patent application CN108250561, entitled “Glass fiber and graphene hybrid filler filled polypropylene composite material and preparation method thereof” filed on December 29, 2016, discloses a material made of glass fiber and graphene hybrid filler coated with a polypropylene-based composite material and a production method thereof, wherein the composition of the composite material varies within the following range: 45-85 parts of polypropylene, 10-50 parts of glass fiber and 0.0001-1 part of graphene.
[0015] Chinese patent application CN105670329, entitled "Method for preparing graphene-modified glass fiber reinforced composite material", filed on April 5, 2016, discloses a graphene-modified glass fiber reinforced composite material. The preparation method comprises the following steps: pre-treating graphene with concentrated acid and adding a silane coupling agent for modification; mixing the modified graphene with polyethylene wax, adding the mixture to liquid resin and mixing evenly, vacuum-introducing the mixture into a glass fiber-filled mold, and curing to obtain a graphene-modified glass fiber reinforced resin-based composite material.
[0016] Although several compositions of glass fiber reinforced polymer rods are known in the prior art, there is a constant need for new materials that are able to withstand greater stresses for use in increasingly demanding reinforced structures.
[0017] The inventors have therefore concluded that producing a polymer rod reinforced with glass fibres and containing a resin mixed with graphene nanoplatelets would provide better resistance and economic advantages compared to materials known in the prior art. Summary of the invention
[0018] The present invention aims to provide a composite polymer rod, which is made of resin and glass fiber reinforced with graphene nanosheets. In a specific embodiment, the resin used is a polyester resin. In additional embodiments, a curing accelerator and a filler can be used when necessary.
[0019] In an additional embodiment, a method is provided for manufacturing a polymer rod containing glass fibers and a resin reinforced with nanosheets (more specifically, graphene nanosheets) by a pultrusion process, which is a continuous manufacturing process using a resin (with or without fillers and / or additives) and a flexible reinforcing material such as glass fibers.
[0020] More preferably, the reinforcing material used in the present invention is based on glass fibers and is divided into "yarn bundles" and mats. As is generally known to those skilled in the art, a "yarn bundle" is like a cable with hundreds of very fine parallel glass filaments, which are responsible for the tensile strength (longitudinal strength) of the pultruded profile.
[0021] In an additional embodiment, the glass fiber is of E-type (E-glass). E-type fibers are obtained from a mixture of oxides of Si, Al, B, Ca and Mg (calcium borosilicate alumina) and are commonly used as a reinforcement material for thermoplastics due to their low cost compared to the cost of aramid and carbon, thereby improving the properties of the resulting material, such as impact resistance and stiffness.
[0022] As is well known to those skilled in the art, the type of resin used determines properties such as corrosion resistance, flame retardancy, maximum operating temperature, and significantly contributes to certain mechanical strength properties of the part (such as impact resistance and fatigue resistance). Several thermosetting resins can be processed by pultrusion, each with its own chemical resistance properties. In a specific embodiment of the present invention, a polyester-based resin is used. In other embodiments, the polyester-based resin is an isophthalic resin, and in a preferred embodiment, the isophthalic resin is reinforced with graphene nanoplatelets (NPG).
[0023] The curing or solidification mechanism of thermosetting liquid resins involves free radical, cationic or hybrid polymerization mechanisms, which form a highly cross-linked polymer structure by providing an appropriate form of energy, such as heat, light or electrical potential.
[0024] Technical issues
[0025] Although many technologies (such as those described above for the prior art) provide solutions for reinforcing polymer profiles with glass fibers, there is still a need for high-quality and low-manufacturing-cost profiles. High-value-added resins, such as epoxy resins, are commonly used in the technical field. Therefore, the object of the present invention is to provide new profiles comprising glass fibers and resins reinforced with graphene nanosheets, which have a lower production cost than the materials known in the prior art and have satisfactory mechanical properties for use in industry (e.g., for civil industry).
[0026] Advantages of the invention
[0027] An advantage of the present invention is that, compared to glass fiber reinforced polymer profiles available in the prior art, similar or improved quality is achieved using lower cost resins (such as polyester resins) reinforced with graphene nanoplatelets relative to higher cost resins (e.g., epoxy resins or vinyl ester resins). In alternative embodiments, for illustrative purposes, formulations comprising epoxy resins and graphene nanoplatelets are also proposed in the examples. In the case of adding graphene nanoplatelets to polyester / epoxy resins, the obtained product is the same or better in quality than the products known on the market, but more competitive in cost. Satisfactory results are also obtained for tensile strength, elastic modulus and properties inherent to thermosetting plastics (such as durability, non-oxidizability, non-conductivity and non-conductive magnetism), as will be shown throughout this article.
[0028] The inventors surprisingly found that adding graphene nanosheets dispersed in a solvent (such as n-methylpyrrolidone) to a polyester resin impregnated with reinforcing fibers (such as glass fibers) obtained mechanical properties similar to those required (tensile strength) or even higher (elastic modulus), so the reinforced polymer rods of the present invention can be used in extremely demanding devices (such as those used in civil engineering). As will be understood by those skilled in the art, if the dispersion of the nanosheets in the resin is satisfactory, the same effect can be verified when using other polymer resins (such as epoxy resins).
[0029] Another advantage of the present invention is the ability to provide reinforced polymer rods to replace steel bars available on the market, such as CA 50 and CA 60, in various applications, which, apart from the manufacturing cost, also presents the major advantage of being able to build lighter structures. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Features of the various aspects are particularly set forth in the appended claims. However, the various aspects, both as to organization and method of operation, together with additional objects and advantages thereof, may be better understood by reference to the following description when considered in conjunction with the accompanying drawings, as shown below.
[0031] Figure 1 A schematic flow chart of a method for producing a polymer rod containing glass fibers according to a first embodiment of the present invention is depicted.
[0032] Figure 2 A pultrusion process for obtaining a polymer rod containing glass fibers and graphene nanosheets according to an embodiment of the present invention is illustrated.
[0033] Figure 3 A rack with a set of fiber yarn bundles (1) according to the invention is shown.
[0034] Figure 4An exemplary resin bath (2) according to the present invention is shown.
[0035] Figure 5 An impregnated fiber is shown passing through a die according to one embodiment of the present invention.
[0036] Figure 6 An exemplary furnace (4) for use in the present invention is shown.
[0037] Figure 7 A fiber pulling device (5) according to one embodiment of the present invention is shown.
[0038] Figure 8 An exemplary reel is shown for reeling a rod (M3) obtained by the method of the invention. DETAILED DESCRIPTION
[0039] In a first embodiment of the present invention, a method for producing a polymer rod is disclosed, the method comprising coating a plurality of long fibers (such as glass fibers) with a polymer composition comprising at least one resin (such as polyester or epoxy resin) and a reinforcing filler, wherein the method comprises the following steps:
[0040] a. In the pultrusion process, a plurality of long reinforcing fibers (M1) to be coated with a resin and a nanosheet composition (BR) are provided to a resin bath (2) by means of a roller (1);
[0041] b. preparing a resin and nanosheet composition (BR), wherein the nanosheet may be present in a ratio of 0.01% to 0.1% by weight of the composition;
[0042] c. placing the resin and nanosheet composition (BR) in the resin bath (2), wherein the resin and nanosheet composition are maintained at a temperature range of 20°C to 30°C;
[0043] d. providing a polymerization furnace (4) which is fluidically connected upstream of the resin bath (2) and maintained at a temperature between 100°C and 170°C;
[0044] e. Drawing the plurality of fibers coated with the resin and nanosheet composition (M2) by means of a drawing device (5) fluidically connected downstream of the polymerization furnace (4), wherein the fibers impregnated with the resin and nanosheet composition (M2) enter the polymerization furnace (4) and stay in the polymerization furnace (4) for 2 to 4 minutes until the resin and nanosheet composition (BR) are cured, thereby forming a cured polymer rod containing glass fibers and the resin having graphene nanosheets (M3);
[0045] Wherein, the resin of the resin composition (BR) is selected from polyester resin, epoxy resin or vinyl ester resin; and wherein the nanosheets are produced from graphene.
[0046] In a specific embodiment, the size of the graphene nanosheets is between 6 and 8 nm. In a specific embodiment, the graphene nanosheets are dispersed in a solvent. In a specific embodiment of the present invention, the graphene nanosheets are received in a solution containing graphene nanosheets, wherein the solvent used in the solution is N-methylpyrrolidone.
[0047] In a specific embodiment of the present invention, the solvent containing graphene nanosheets is n-methylpyrrolidone (NMP, CAS No. 872-50-4N) with a molecular formula of C5H9NO. Those skilled in the art will appreciate that any other solvent suitable for dissolving the nanosheets of the present invention may be used alternatively, as long as the solvent does not interfere with the expected properties of the resin composition disclosed in the present invention.
[0048] In a specific embodiment, the temperature of the polymerization furnace (4) of step d) depends on the size of the rods produced. In a specific embodiment, the diameter of the rods is between 4 mm and 30 mm.
[0049] In an alternative embodiment, the resin of the polymer composition is a polyester resin, more specifically an isophthalic acid resin containing neopentyl glycol (NPG).
[0050] In a second embodiment of the present invention, there is provided a polymer rod reinforced with glass fibers and graphene nanoplatelets, comprising:
[0051] a. a plurality of glass fibers; and
[0052] b. Resin and graphene nanosheet composition.
[0053] In a preferred embodiment, the ratio of the plurality of glass fibers to the resin and graphene nanoplatelet composition is about 75:25 to 85:15 based on weight.
[0054] In one embodiment, the average size of the nanosheets is 6 nm to 8 nm.
[0055] In an exemplary embodiment of the present invention, the preparation of the resin composition comprises the following steps:
[0056] a. Weigh 10kg to 12kg of resin and place it in a container;
[0057] b. Weigh 200 g to 240 g of calcite and add it to the container containing the resin;
[0058] c. Stir the resin and calcite with a stirrer for 10 minutes;
[0059] d. Weigh 80 g to 90 g of BPO and add it to the mixture;
[0060] e. Stir the mixture for 3 min;
[0061] f. Weigh 40 g to 60 g of cobalt and add it to the mixture;
[0062] g. Stir the mixture for 3 min;
[0063] h. Weigh 200 g to 300 g TBP and 10 g to 20 g graphene solution and add them to the mixture;
[0064] i. Stir the mixture for 10 min;
[0065] j. Fill the tank with the stirred mixture produced in step i.
[0066] Figure 3 A rack with a set of fiber yarn bundles according to the invention is shown.
[0067] Figure 4 An exemplary resin bath according to the present invention is shown.
[0068] Figure 5 The threading of resin-impregnated fibers according to one embodiment of the present invention is shown.
[0069] Figure 6 An exemplary furnace for use in the present invention is shown.
[0070] Figure 7 A fiber tensioner according to an embodiment of the present invention is shown.
[0071] Figure 8 An exemplary reel is shown for reeling the rod obtained by the method of the invention.
[0072] Examples
[0073] Example 1:
[0074] Step 1: Preparation of polyester resin and graphene nanosheet composition
[0075] In an exemplary embodiment of the present invention, the following ingredients are mixed to make a resin composition:
[0076] a. Isophthalic acid polyester resin containing neopentyl glycol (NPG) (CAS-100-42-5)
[0077] b. Tert-butyl perbenzoate (TBPB) in liquid form
[0078] i. Methyl ethyl ketone peroxide (CAS1338-23-4)
[0079] ii. Dimethyl phthalate (CAS131-11-3)
[0080] iii. Methyl ethyl ketone (CAS 78-93-3)
[0081] c. Tert-butyl perbenzoate (TBPB) in liquid form
[0082] i. Methyl ethyl ketone peroxide (CAS1338-23-4)
[0083] ii. Dimethyl phthalate (CAS131-11-3)
[0084] iii. Methyl Ethyl Ketone - CAS 78-93-3
[0085] d. BPO-dibenzoyl peroxide (CAS 94-36-0, 50%)
[0086] iv. Phthalates (CAS-84-69-5, 15%-27%)
[0087] v. Hydrogenated vegetable oil (CAS 8001-78-3, 10%-12%)
[0088] vi. Nonionic surfactant (CAS-9038-95-3, 8%-10%)
[0089] e. Cobalt-Acepol 6%-Aliphatic solvent (CAS 8052-41-3)
[0090] vii. Cobalt octanoate (CAS13586-82-8)
[0091] f. Calcite - calcium carbonate - Ca Mg(CO3)2
[0092] Then, graphene nanosheets dispersed in an N-methylpyrrolidone (NPM) solvent were added to the resin composition.
[0093] i. Graphene (CAS-1034343-98-0) (minimum purity 93.2%, manufactured by UCSGRAFENE);
[0094] ii. N-Methylpyrrolidone (NPM) (872-50-4)
[0095] In an exemplary embodiment, the amounts of the components constituting the resin and graphene nanosheet composition are specifically shown in Table 1:
[0096] Table 1: Ingredients for preparing polyester resin and nanosheet compositions Element Quantity(g) Weight % (about mixing) 1 Resin 12000 90-95 2 TBPB 300 1-4 3 BPO 84 0.2-1.4 4 cobalt 48 0.1-0.8 5 Calcite 240 1-10 6 Graphene solution in NPM 120 0.1-2
[0097] In a more specific embodiment, the preparation of the composition comprising a polyester resin and graphene nanosheets is carried out according to the following method:
[0098] a. Weigh 12 kg of resin and place it in a container;
[0099] b. Weigh 240 g of calcite and add it to the container containing the resin;
[0100] c. Stir the resin and calcite with a stirrer for 10 minutes;
[0101] d. Weigh 84 g of BPO and add it to the mixture;
[0102] e. The resulting mixture was stirred for 3 min;
[0103] f. Weigh 48 g of cobalt and add it to the mixture;
[0104] g. The resulting mixture was stirred for 3 min;
[0105] h. Weigh 300 g TBP and 120 g graphene nanosheets and add them to the mixture; and
[0106] I. The obtained resin and graphene nanosheet composition was stirred for 10 minutes.
[0107] The resulting resin and graphene nanosheet composition placed in the resin bath (2) must be maintained at a temperature between 20°C and 30°C.
[0108] Step 2: Impregnating the glass fiber with the resin and graphene nanosheet composition
[0109] The impregnation of glass fibers (TEX 2200, 4400 and 8800 from manufacturers Owens Cornnig, CPIC or Jushi) with the resin and graphene nanosheet composition is accomplished by a pultrusion process, wherein the glass fibers are pulled from their reels (yarn bundles), wherein a plurality of fibers are passed through a rod to remove excess resin and to orient them (6), which keeps the plurality of glass fibers immersed in a resin bath (2), such that the glass fibers (M1) are impregnated with the resin and graphene nanosheet composition prepared according to the process described in the previous step.
[0110] In this example, the E-glass fiber used is obtained from a mixture of oxides of Si, Al, B, Ca and Mg (calcium borosilicate alumina) and is commonly used as a reinforcement material for thermoplastics due to its low cost compared to aramid and carbon reinforcements, thereby improving material properties (such as impact resistance and stiffness).
[0111] The type of resin used determines properties such as corrosion resistance, flame retardancy, maximum operating temperature, and significantly contributes to certain mechanical strength properties of the part (such as impact resistance and fatigue resistance). Several thermosetting resins can be processed by pultrusion, each with its own chemical resistance properties. In the present invention, an isophthalic polyester resin containing NPG is used. Other resins such as epoxy resins and vinyl esters can also be used in the present composition.
[0112] The residence time of the plurality of glass fibers (M1) in the resin and graphene nanosheet composition (BR) is adjusted to 10-12 min.
[0113] Step 3: Curing process of glass fiber and graphene nanosheet reinforced polymer rods
[0114] Then, the fibers impregnated with the resin and graphene nanosheet composition are pulled from the resin bath to the polymerization furnace (4) by a pulling device (5), and in the polymerization furnace (4), the resin and nanosheet composition impregnated between the plurality of glass fibers are solidified to form a polymer rod (M3) reinforced with glass fibers and graphene nanosheets.
[0115] A die (not shown) is located upstream of the polymerization oven (5), through which a plurality of impregnated glass fibers (M2) pass before entering the polymerization oven (5), and the die (not shown) defines the dimensions of the cured polymer rods (M3) to be exited downstream from the polymerization oven (5).
[0116] Through the pultrusion process, the solidified polymer rod (M3) is formed into a continuous flexible rod, which can then be wound on a reel (not shown) for storage and / or future commercialization.
[0117] Example 2:
[0118] In an alternative embodiment of Example 1, this Example 2 uses epoxy resin as the manufacturing resin. In a more specific embodiment, the reinforcing resin is prepared according to the following Table 2:
[0119] Table 2: Composition of the reinforced resin produced according to Example 2. product Quantity (kg) Araldite GY 260 10 Aradur HY 2918 7 Accelerator 960-1 0.5 Araldite DY-E 0.5 Graphene 0.01
[0120] Among them, the products in Table 2 adopt the following technical specifications:
[0121] a. GY 260: Unmodified high viscosity liquid epoxy resin based on bisphenol, CAS No.: 25068-38-6;
[0122] b. HY 2918 or CW 1457-2, methyltetrahydrophthalic anhydride, CAS No.: -11070-44-3 90-100;
[0123] c. Accelerator 960-1, tertiary amine accelerator, used in high ambient temperature and epoxy resin curing system, components:
[0124] i. 2,4,6-Tris(dimethylaminomethyl)phenol (CAS No.: 90-72-2); concentration: 70-90 (% w / w);
[0125] ii. Bis[(dimethylamino)methyl]phenol (CAS No.: 71074-89-0); concentration: 10-20 (% w / w);
[0126] d. DY-E: Ethylene oxide, mono[(C12-14-alkyloxy)methyl]-glycidyl ether derivative of C12-C14 alcohol (CAS No.: 68609-97), concentration: 90-100 (% w / w);
[0127] e. Graphene: nanosheets in solution as described previously in Example 1.
[0128] In an even more specific embodiment, the preparation of the composition comprising epoxy resin and graphene nanoplatelets is carried out according to the following method:
[0129] a. heating the Araldite GY 260 epoxy resin to a temperature of 45°C to 55°C;
[0130] b. Weigh 10 kg of heated Araldite GY 260 resin;
[0131] c. Weigh 7kg of Aradur HY 2918 component;
[0132] d. Araldite GY 260 and Aradur HY 2918 resins were mixed and stirred in a rotary mixer for 3 min;
[0133] e. Weigh 0.5kg 960-1 accelerator;
[0134] f. Weigh 0.5kg Araldite DY-E;
[0135] g. Weigh 100 ml of graphene solution;
[0136] h. 0.5 kg of accelerator 960-1, 0.5 kg of Araldite DY-E and 100 ml of graphene solution were added to the pre-stirred mixture of Araldite GY 260 and Aradur HY 2913;
[0137] i. Stir all components for 3 minutes;
[0138] j. Place the finished resin into a tank and start the pultrusion process.
[0139] result
[0140] The mechanical properties of polyester polymer rods reinforced with glass fibers and graphene nanosheets were tested and satisfactory results were obtained.
[0141] Ten samples were extracted from the polymer rods reinforced with glass fiber and graphene manufactured according to the method of the present invention and provided to the Institute of Performance and Civil Construction Technology - ITT Performance of West North Valley University on November 10, 2021 for performance analysis of these rods. The tensile strength properties, tensile elastic modulus and effective diameter of the glass fiber and graphene reinforced polymer rods described in Item 4 were analyzed according to ASTM D7205:2006 and ASTMD 792:2020.
[0142] For density testing, 5 samples were analyzed to determine the average property.
[0143] Table 3 - Density results for graphene nanoplatelets reinforced polyester rods prepared according to Example 1.
[0144] in:
[0145] -a = air dry mass (g);
[0146] -b = mass completely immersed in water (g);
[0147] -D23C = density of each sample (kg / m 3 );
[0148] -D23C med = Average density of the sample (kg / m 3 );
[0149] -S n-1 = sample standard deviation;
[0150] -CV = coefficient of variation of the results;
[0151] -
[0152] -
[0153] For the tensile strength test, 5 specimens were analyzed to determine the average property.
[0154] Table 4 - Tensile Strength Results
[0155] in:
[0156] -
[0157] -Pm ax = maximum load applied to the specimen;
[0158] -F tu = tensile strength of the specimen;
[0159] -F tu,med = average resistance of the specimen;
[0160] -s n-1 = sample standard deviation;
[0161] - CV = coefficient of variation of the result.
[0162] For the static elastic modulus test, five specimens were analyzed to determine the average property.
[0163] Table 5 - Results of static elastic modulus
[0164] in:
[0165] -E chord = tensile elastic modulus of the specimen;
[0166] -E chord,med = the average value of the elastic modulus results;
[0167] -s n-1 = sample standard deviation;
[0168] - CV = coefficient of variation of the result.
[0169] The tensile strength and elastic modulus of the resulting rods compared to the minimum requirements for civil engineering use
[0170] The obtained rods were analyzed according to current standards, giving the following results for tensile strength and elastic modulus:
[0171] Table 6: Resistance obtained for polymer rods according to the invention
[0172] It can be seen from the data shown in Table 6 that the tensile strength and elastic modulus results exceed the minimum requirements specified in ASTM and ACI440 standards, which confirms that the rod produced according to the production method of the present invention can withstand great stress and is suitable for civil engineering, for example.
[0173] Comparison between the rods obtained in the present invention and prior art steel bars
[0174] Compared to the CA 50 / 60 steel bars of the prior art, the rods obtained by the pultrusion process described herein show the following advantages:
[0175] Table 7: Comparative analysis of the properties of the rod obtained by the method of the present invention and the steel obtained by the prior art:
[0176] It can be clearly seen from Table 7 that the technical characteristics of polymer rods reinforced with glass fibers and graphene nanoplatelets exceed those of materials commonly used for high stress applications in civil engineering (such as CA 50 / CA 60 steel). In addition to excellent resistance, the material obtained according to the present invention also has the advantages of light weight (convenient for logistics and storage), corrosion resistance, low thermal conductivity, etc.
[0177] The embodiments of the present invention have been described in detail above with reference to the drawings, but the specific configuration is not limited to these embodiments and also includes, for example, modifications to the design within a range not departing from the scope of the present invention.
[0178] Within the scope of a certain aspect of the present invention defined by the claims, various modifications may be made, and embodiments produced by appropriately combining the technical means disclosed according to different embodiments are also included in the technical scope of the present invention. The technical scope of the present invention also includes configurations in which the constituent elements described in the embodiments and having the same effects as each other are replaced with each other.
Claims
1. A method for producing a polymer rod, comprising: coating the plurality of long fibers with a polymer composition comprising at least one resin selected from the group consisting of a polyester resin and an epoxy resin; and at least one reinforcing filler; wherein the method is characterized by comprising the following steps: a. By means of a roller (1), a plurality of long reinforcing fibers (M1) to be coated with a resin composition (BR) containing a nanosheet-type reinforcing filler is provided in a resin bath (2); b. preparing a resin and nanosheet composition (BR), wherein the nanosheet is present in an amount of 0.01% to 0.1% by weight of the composition; c. placing the resin and nanosheet composition (BR) in the resin bath (2), wherein the resin and nanosheet composition are maintained at a temperature range of 20°C to 30°C; d. providing a polymerization furnace (4) which is fluidically connected upstream of the resin bath (2) and maintained at a temperature between 100°C and 170°C; e. Drawing the plurality of fibers coated with the resin and nanosheet composition (M2) by means of a drawing device (5) fluidically connected downstream of the polymerization furnace (4), wherein the fibers impregnated with the resin and nanosheet composition (M2) enter the polymerization furnace (4) and remain in the polymerization furnace (4) for a residence time of 2 to 4 minutes until the resin and nanosheet composition (BR) solidifies, thereby forming a solidified glass fiber polymer rod with graphene nanosheets (M3); Among them, nanosheets are produced from graphene.
2. The method according to claim 1, characterized in that The size of the graphene nanosheets is between 6nm and 8nm.
3. The method according to claim 1 or 2, characterized in that: The graphene nanosheets are dispersed in a solvent.
4. The method according to claim 3, characterized in that The solvent containing the graphene nanosheets is N-methylpyrrolidone.
5. The method according to any one of the preceding claims, characterized in that The polyester resin is an isophthalic acid resin containing neopentyl glycol (NPG).
6. A polymer rod comprising: Glass fiber impregnated with a composition comprising a resin and at least a reinforcing filler, characterized in that the resin is selected from polyester resin and epoxy resin; the resin composition contains graphene nanosheets, and the amount of the graphene nanosheets is 0.01% to 0.1% by weight relative to the weight of the composition containing the resin.
7. The polymer rod according to claim 6, characterized in that The ratio of the plurality of glass fibers to the resin and graphene nanosheet composition is about 75:25 to 85:15 based on weight.
8. The polymer rod according to claim 6, characterized in that The average size of the nanosheets is 6 nm to 8 nm.
9. A polymer rod obtained by the process as claimed in claim 1.
10. The polymer rod according to any one of claims 6 to 9, characterized in that The polymer rod has a tensile strength greater than 800 MPa and an elastic modulus greater than 50 GPa.
11. The polymer rod according to any one of claims 6 to 9, characterized in that The polymer rods are used in construction or civil engineering.
12. The polymer rod according to any one of claims 6 to 9, characterized in that The polymer rods are produced by a pultrusion process.
13. The polymer rod according to any one of claims 6 to 12, characterized in that The resin is a polyester resin.
14. The polymer rod according to any one of claims 6 to 12, characterized in that The resin is epoxy resin.